Fully-conjugated three-dimensional covalent organic polymer, preparation and application of fully-conjugated three-dimensional covalent organic polymer as lithium ion battery positive electrode material
By applying the Knoevenagel reaction to synthesize carbon-carbon double bonds of the Knoevenagel reaction in the positive electrode of the lithium-ion battery, the problem of restricted charge transfer of two-dimensional materials is solved and the high stability of lithium-ion batteries is achieved and capacity performance improvement.
Patent Information
- Application Number
- CN202411311718.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The existing two-dimensional covalent organic polymers have the problem of limited conductivity in charge transport, especially in the direction perpendicular to the π conjugation plane, which affects the overall performance of the material.
A fully π-conjugated three-dimensional covalent organic polymer material synthesized by the Knoevenagel reaction is developed, using saddle-like cyclooctanotetraene tetrathiophene derivative ligand and S-indole-1,3 ,5,7(2H,6H)-tetraone reacts to form a three-dimensional structure rich in lithium ion redox active sites, and is applied to the positive electrode of lithium ion batteries.
The performance of lithium-ion battery with high stability and high capacity was achieved. The discharge capacity at 0.1A·g-1 current density reached 238.3mAh·g-1. After 200 cycles, the Coulomb efficiency was 99.61%, and it showed that it was found at different current density. Good capacity retention and reversibility.
Smart Images

Figure CN119192502A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of covalent organic polymer porous materials, and specifically relates to the preparation of a novel three-dimensional fully π-conjugated organic polymer material connected by carbon-carbon double bonds (C=C). The three-dimensional covalent organic polymer can be applied to the positive electrode field of lithium-ion batteries and the like, and effectively improves the stability and charge and discharge capacity of lithium-ion batteries. Background Art
[0002] Covalent organic polymers (COPs) are a class of porous organic materials formed by connecting multiple organic structural units through covalent bonds. Due to their high adsorption capacity, large surface area, high porosity, chemical adjustability, high stability and easy synthesis, they have aroused widespread interest and developed rapidly. They have a wide range of applications in drug delivery, separation technology, chemical sensors, gas storage, catalysis, optoelectronics, energy storage, biomedical products and other fields. (New J.Chem., 2020, 44, 12331).
[0003] COPs can polymerize organic ligands with functional groups containing specific active sites into multidimensional and multifunctional organic porous materials through covalent bonds. Currently, most reports are of fully conjugated two-dimensional COPs, which improve the lithium storage capacity of the material by introducing groups that can serve as lithium ion active sites, such as carbonyl groups (C=O). For example, in 2021, Chen's team constructed a two-dimensional COP containing a large number of C=O active sites using 2,7-dibromo-4,5,9,10-pyrenetetraone and 1,3,5-benzenetricarboxylic acid as ligands, and successfully applied it to the positive electrode of lithium-ion batteries. After the COP was made into a lithium battery positive electrode material, it showed excellent long-cycle stability performance at a current density of 0.1 A·g -1 When the battery is charged, it has 224mAh g -1 The battery has a considerable capacity, and the capacity retention rate is close to 95% after 1400 cycles. (J. Mater. Chem. A, 2021, 9, 2700).
[0004] Compared with two-dimensional materials, the research on three-dimensional materials is relatively less. For two-dimensional COPs, charges can be quickly transferred and delocalized on the π-conjugated plane. However, in the z direction perpendicular to the xy conjugated plane, the charge transfer is hindered due to the lack of effective conjugated connection between layers, which greatly affects the conductivity of the COP material. The fully conjugated three-dimensional COP effectively improves the charge transfer performance of the material by increasing the π conjugation degree in dimension. Therefore, the development of new three-dimensional fully conjugated COPs for application in batteries and other fields has important research significance. To this end, we constructed a new three-dimensional COP material connected by fully conjugated carbon-carbon double bonds (C=C), and applied this material in the field of lithium-ion battery positive electrodes, which has excellent cycle stability and charge and discharge capacity.
[0005] Exploring the preparation of three-dimensional fully conjugated covalent organic polymers and their application in lithium-ion battery positive electrodes is of great research significance for promoting the development of efficient, green and sustainable batteries. Summary of the invention
[0006] The objects of the present invention are:
[0007] First, a method for synthesizing a fully π-conjugated three-dimensional covalent organic polymer material connected by carbon-carbon double bonds and having abundant lithium ion redox active sites is provided.
[0008] Second, fully π-conjugated three-dimensional covalent organic polymer materials containing rich lithium ion redox active sites are applied in the field of lithium-ion battery positive electrodes.
[0009] A three-dimensional covalent organic polymer, characterized in that the structural formula is as follows:
[0010] The wavy line represents the continuation of the structure. The terminal carbon-carbon double bonds are connected;
[0013] in It represents an aromatic ring, an aromatic heterocyclic ring of hybridization such as O / S / Se, and the aromatic ring is benzene, naphthalene, and the like.
[0014] like Can be R is a hydrogen atom, C 1-20 or alkyl groups or other substituents (aryl, substituted aryl, halogen, nitro, etc.).
[0015] The first aspect of the present invention provides a method for synthesizing a fully π-conjugated three-dimensional covalent organic polymer material connected by carbon-carbon double bonds, and the synthesis steps are as follows:
[0016] (1) A saddle-shaped cyclooctatetraene tetrathiophene derivative ligand substituted with an aromatic heterocycle, COThP-CHO, and S-indole-1,3,5,7(2H,6H)-tetraone (ICTO) are dissolved in an organic solvent, and then a catalyst, pyridine, is added; wherein COThP-CHO is a saddle-shaped cyclooctatetraene tetrathiophene derivative ligand, wherein the aromatic heterocycle can be selected from a benzene ring, furan, thiophene, selenophene, or other aromatic heterocycles.
[0017] (2) The reaction system is briefly sonicated to allow for full mixing and dispersion, followed by a freeze-vacuum-thaw cycle, and then sealed and heated to complete the reaction;
[0018] (3) The product is filtered, washed, and purified by extraction to obtain a three-dimensional covalent organic polymer with a fully conjugated structure connected by carbon-carbon double bonds (named BUCT-COP-8).
[0019] The structural formula of the saddle-shaped ring-shaped octatetraene tetrathiophene derivative ligand COThP-CHO is as follows: It represents an aromatic ring, an aromatic heterocyclic ring of hybridization such as O / S / Se, and the aromatic ring is benzene, naphthalene, and the like.
[0020] like Can be Etc. aromatic heterocycles.
[0021]
[0022] Furthermore, in the step (1), the molar ratio of COThP-CHO to S-indole-1,3,5,7(2H,6H)-tetraketone (ICTO) is 1:1 to 10, and the optimal ratio is 1:2.
[0023] Furthermore, in step (1), the solvent is a mixed solvent of n-butanol (n-BuOH) and o-dichlorobenzene (o-DCB).
[0024] Furthermore, in step (1), the mixed solvent is a mixed solvent of n-butanol and o-dichlorobenzene in a volume ratio of 0-10:10-0 (the optimal volume ratio is 1:1).
[0025] Furthermore, in the step (1), the amount of the catalyst pyridine used is 0 to 1 mL (the optimal volume is 0.15 mL) per 0.015 mmol of COThP-CHO.
[0026] Furthermore, in the step (2), the ultrasonic time is 1 to 30 minutes, and the freeze-vacuum-thaw cycle method is: freezing the reactants with liquid nitrogen, evacuating the air, and thawing them with nitrogen.
[0027] Furthermore, in the step (2), the temperature of the heating reaction is between 50 and 200° C., and the reaction time is between 1 and 10 days.
[0028] Furthermore, in the step (3), multiple Soxhlet extractions are performed with organic solvents such as dichloromethane, acetone, tetrahydrofuran, etc., each extraction lasting 1 to 3 days until the solvent becomes colorless, and finally the solid is collected and vacuum dried to obtain a fully π-conjugated three-dimensional covalent organic polymer connected by carbon-carbon double bonds.
[0029] The present invention uses Knoevenagel reaction to react fully conjugated organic ligand COThP-CHO with s-indole-1,3,5,7(2H,6H)-tetraketone (ICTO) to synthesize fully conjugated three-dimensional COP material BUCT-COP-8 for the first time. The synthesis route is as follows:
[0030]
[0031] Can be The substituent R on ICTO can be a hydrogen atom, C 1-20 etc. alkyl or other substituents.
[0032] The second aspect of the present invention is that the material prepared by the preparation method of the fully conjugated three-dimensional covalent organic polymer material synthesized by the above method is applied to the positive electrode of a lithium ion battery and a battery test is performed, comprising the following steps: dispersing the fully conjugated covalent organic polymer (BUCT-COP-8), Ketjen black and polyvinylidene fluoride (PVDF) prepared by the present invention in a certain proportion in N-methylpyrrolidone (NMP) to form a slurry, loading it on a copper foil, and vacuum drying it at a certain temperature, using it as the positive electrode, a lithium sheet as the counter electrode, lithium hexafluorophosphate + EC / DMC as the electrolyte, and a polyethylene film as a diaphragm, assembling the battery in an argon atmosphere glove box, placing the front cover, the positive electrode sheet, and the diaphragm in order, after dripping the lithium hexafluorophosphate + EC / DMC electrolyte, putting the lithium sheet, gasket, and gasket, and then covering the back cover for tableting, and placing it for 12-24 hours so that the electrolyte fully contacts the electrodes to make a BUCT-COP-8 battery for performance testing.
[0033] Furthermore, the slurry ratio is BUCT-COP-8: Ketjen black: polyvinylidene fluoride mass ratio = 1-8:8-1:1-8 (the optimal ratio is 7:2:1).
[0034] Furthermore, the loading amount of the slurry on the copper foil is 0.5 to 2 mg / cm 2 .
[0035] Furthermore, the vacuum drying temperature of the material is 30-60°C (the optimal temperature is 40°C).
[0036] Furthermore, the material is tested for battery capacity and charge-discharge cycle stability in a blue-electric test system.
[0037] The advantages of the present invention are:
[0038] (1) The present invention successfully synthesizes a highly stable, fully conjugated, three-dimensional saddle-shaped covalent organic polymer material linked by carbon-carbon double bonds in one step for the first time through the Knoevenagel reaction, and applies it to the field of lithium-ion battery positive electrodes.
[0039] (2) The fully conjugated three-dimensional covalent organic polymer BUCT-COP-8 prepared by the present invention has shown high stability and capacity when applied to lithium-ion batteries, 0.1A·g -1 The discharge capacity of BUCT-COP-8 battery can reach 238.3 mAh g -1 After 200 cycles, the Coulomb efficiency is 99.61% at 1A·g -1 After 1000 cycles, the discharge capacity is 122.4 mAh g -1 After 1000 cycles, the coulombic efficiency was 99.90% and the capacity retention rate was 98.96%. In the rate test, 0.1, 0.2, 0.5, 1.0 and 2.0, 0.1A·g -1 The discharge battery capacities at the current densities are 234, 204, 155, 121, 92, and 218 mAh g -1 When the current density returns to 0.1A·g -1 When the battery is fully charged, it can be restored to 218 mAh g -1 reversible capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is the infrared absorption spectrum (FT-IR) of the three-dimensional covalent organic polymer (BUCT-COP-8) prepared in the present invention.
[0041] Figure 2 X-ray photoelectron spectroscopy (XPS) of the three-dimensional covalent organic polymer (BUCT-COP-8) prepared in the present invention.
[0042] Figure 3 The solid-state nuclear magnetic spectrum of the three-dimensional covalent organic polymer (BUCT-COP-8) prepared in the present invention.
[0043] Figure 4 The nitrogen adsorption-desorption curve and pore size distribution diagram of the three-dimensional covalent organic polymer (BUCT-COP-8) prepared in the present invention.
[0044] Figure 5The cyclic voltammetry (CV) curve of the three-dimensional covalent organic polymer (BUCT-COP-8) prepared in the present invention.
[0045] Figure 6 This is the impedance spectrum of the three-dimensional covalent organic polymer (BUCT-COP-8) prepared in the present invention.
[0046] Figure 7 This is the long cycle charge and discharge stability curve of the three-dimensional covalent organic polymer (BUCT-COP-8) prepared in the present invention.
[0047] Figure 8 The three-dimensional covalent organic polymer (BUCT-COP-8) prepared by the present invention is assembled into a battery and subjected to constant current charge and discharge curves.
[0048] Fig. 9 Rate test of a battery after the three-dimensional covalent organic polymer (BUCT-COP-8) prepared by the present invention is assembled into a battery. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. However, the protection scope of the present invention is not limited to the following examples.
[0050] Example 1
[0051] The synthesis steps of a three-dimensional fully conjugated covalent organic polymer (BUCT-COP-8) rich in carbonyl groups connected by carbon-carbon double bonds are as follows:
[0052] Weigh COThP-CHO (0.015mmol) and s-indole-1,3,5,7(2H,6H)-tetraketone (ICTO) (0.03mmol) and add them to a Pyrex tube. Add 0.5mL of n-butanol (n-BuOH) and 0.5mL of o-dichlorobenzene (o-DCB) to the tube, then ultrasonically treat it to mix it evenly. Add catalyst pyridine (0.15mL) and ultrasonically treat it for 10 minutes to make it evenly dispersed. Then seal the thick mouth of the Pyrex tube, connect nitrogen to the narrow mouth, and repeat the evacuation and thawing several times. After tightening the tube, place the Pyrex tube in an oven and let it stand. Raise the temperature from room temperature to 50℃~200℃ and keep it for 12-72 hours to carry out the thermal polycondensation reaction. After the reaction is completed, place it in an oven to cool naturally. In order to remove the unreacted ligands and small organic molecules in COP, tetrahydrofuran, 1,4-dioxane, dichloromethane and other organic solvents are used for filtration and washing in sequence, and then collected in a paper bag and placed in a Soxhlet extractor, and tetrahydrofuran is refluxed and soaked to further remove small organic molecules in COP. At the same time, the solvents used for extraction are changed many times, including dichloromethane, acetone and other solvents, and the total extraction is more than three days. After the paper bag is taken out and dried, the COP in the paper bag is collected and placed in a drying oven for further drying to remove the solvent. A brown-black powder solid is obtained.
[0053] Figure 1 and Figure 2 They are infrared spectrum and X-ray photoelectron spectrum. The wavelength in the infrared spectrum is 1720.19cm -1 The typical carbonyl band at 284.5 eV in the XPS spectrum proves the successful introduction of ICTO. The peak of carbon-carbon double bond formation is at 284.5 eV, which confirms the formation of carbon-carbon double bond connection units and proves the successful synthesis of material BUCT-COP-8.
[0054] Example 2: Assembling a three-dimensional fully conjugated covalent organic polymer BUCT-COP-8 into a lithium-ion battery and performing charge and discharge tests
[0055] The fully conjugated covalent organic polymer (BUCT-COP-8) prepared by the present invention, Ketjen black and polyvinylidene fluoride are dispersed in N-methylpyrrolidone (NMP) in a certain ratio (mass ratio 7:2:1) to prepare a slurry, which is loaded on a copper foil and vacuum dried at a certain temperature. The slurry is used as the positive electrode, a lithium sheet is used as the counter electrode, lithium hexafluorophosphate + EC / DMC is used as the electrolyte, and a polyethylene film is used as a separator. The battery is assembled in an argon atmosphere glove box.
[0056] The BUCT-COP-8 assembled battery has a -1 Cyclic voltammetry (CV) was performed under the conditions of 100 nm, and two groups of redox peaks appeared in the second to fifth cycles, corresponding to the reversible lithiation / deoxygenation reactions of lithium ions and carbonyl groups, such as Figure 5It can be seen that it has good reversibility. The rate test was carried out at different current densities, 0.1, 0.2, 0.5, 1.0 and 2.0, 0.1A·g -1 The discharge battery capacities at the current densities are 234, 204, 155, 121, 92, and 218 mAh g -1 When the current density returns to 0.1A·g -1 When the battery is fully charged, it can be restored to 218 mAh g -1 The reversible capacity (indicating less reversible loss), such as Fig. 9 At 1A·g -1 The long cycle stability test was carried out under the condition of 1000 cycles, and the discharge capacity was 122.4mAh·g -1 After 1000 cycles, the coulombic efficiency is 99.90% and the capacity retention rate is 98.96%. Figure 7 Experiments have shown that three-dimensional fully conjugated covalent organic polymers connected by carbon-carbon double bonds assembled into the positive electrode of lithium-ion batteries have excellent stability and high capacity, which has made important contributions to the application of covalent organic polymers in lithium-ion batteries.
[0057] The above embodiments are merely examples for clearly illustrating the present invention, but they cannot be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. All changes made within the scope of protection of the independent claims of the present invention are within the scope of protection of the present invention.
[0058] Attached Figure 1 Note that the wavelength in the infrared spectrum is 1720.19 cm -1 The carbonyl characteristic peak at confirms the successful introduction of ICTO ligand.
[0059] Attached Figure 2 It can be seen that the formation of C=C (284.6 eV) and the introduction of C=O (287.5 eV) can be seen, and the introduction of C=O (531.8 eV) can also be seen, and its peak intensity is relatively high, which proves the formation of C=C and the successful introduction of C=O in BUCT-COP-8.
[0060] Attached Figure 3 The solid-state NMR spectrum of BUCT-COP-8, based on the number and type of C, further proves the successful synthesis of BUCT-COP-8.
[0061] Attached Figure 4 This indicates that the pores in BUCT-COP-8 are mainly micropores, with a small amount of mesopores or macropores.
[0062] Attached Figure 5 This indicates that the redox reaction in the lithium-ion battery assembled by BUCT-COP-8 has high reversibility.
[0063] Attached Figure 6 This shows that the electrochemical impedance of the BUCT-COP-8 battery continues to decrease, indicating that the battery is continuously activated as the cycle proceeds, exposing more redox active sites, which is beneficial to the battery reaction.
[0064] Attached Figure 7 This shows that the introduction of BUCT-COP-8 into the electrode material provides more active sites for lithium ions, thereby greatly improving the capacity performance of lithium-ion batteries.
[0065] Attached Figure 8 This shows that the redox reaction in the battery has high reversibility.
[0066] Attached Fig. 9 This is a charge and discharge rate test at different current densities. It can be seen that the battery has a considerable capacity at different current densities, and the reversibility of the battery's redox reaction is good.
Claims
1. A fully conjugated three-dimensional covalent organic polymer, characterized in that: The structural formula is as follows: The wavy line represents the continuation of the structure. The terminal carbon-carbon double bonds are connected; in represents an aromatic ring, an aromatic heterocyclic ring such as O / S / Se, etc.; R is a hydrogen atom, C 1-20 etc. alkyl or alkyl substituents or other substituent groups.
2. A fully conjugated three-dimensional covalent organic polymer according to claim 1, characterized in that: The aromatic rings are benzene and naphthalene.
3. A fully conjugated three-dimensional covalent organic polymer according to claim 1, characterized in that: for 4. A method for preparing a fully conjugated three-dimensional covalent organic polymer according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) dissolving an aromatic heterocyclic substituted saddle-shaped cyclooctatetraene tetrathiophene derivative ligand COThP-CHO and S-indole-1,3,5,7(2H,6H)-tetraone (ICTO) in an organic solvent, and then adding a catalyst pyridine; wherein COThP-CHO is a saddle-shaped cyclooctatetraene tetrathiophene derivative ligand; (2) The reaction system is briefly sonicated to allow for full mixing and dispersion, followed by a freeze-vacuum-thaw cycle, and then sealed and heated to complete the reaction; (3) The product is filtered, washed, and then purified by extraction to obtain a three-dimensional covalent organic polymer with a fully conjugated structure connected by carbon-carbon double bonds (named BUCT-COP-8); 。 5. The method according to claim 4, characterized in that In the step (1), the molar ratio of COThP-CHO to S-indole-1,3,5,7(2H,6H)-tetraketone (ICTO) is 1:1-10, and the optimal ratio is 1:
2.
6. The method according to claim 4, characterized in that In the step (1), the solvent is a mixed solvent of n-butanol (n-BuOH) and o-dichlorobenzene (o-DCB); the volume ratio of the mixed solvent of n-butanol and o-dichlorobenzene is 0-10:10-0 (the optimal volume ratio is 1:1).
7. The method according to claim 4, characterized in that In step (1), the amount of the catalyst pyridine used is 0-1 mL (the optimal volume is 0.15 mL) per 0.015 mmol of COThP-CHO.
8. The method according to claim 4, characterized in that In the step (2), the ultrasonic time is 1 to 30 minutes, and the freeze-vacuum-thaw cycle method is: freezing the reactants with liquid nitrogen, evacuating the air, and thawing them with nitrogen. In the step (2), the temperature of the temperature rise reaction is between 50 and 200° C., and the reaction time is 1 to 10 days. In the step (3), multiple Soxhlet extractions are performed with organic solvents such as dichloromethane, acetone, tetrahydrofuran, etc., each extraction lasting 1 to 3 days until the solvent becomes colorless. Finally, the solid is collected and vacuum dried to obtain a fully π-conjugated three-dimensional covalent organic polymer connected by carbon-carbon double bonds.
9. Use of a fully conjugated three-dimensional covalent organic polymer as claimed in any one of claims 1 to 3 as a positive electrode material for a lithium ion battery.
10. A lithium ion battery, characterized in that: The positive electrode comprises a fully conjugated three-dimensional covalent organic polymer as described in any one of claims 1 to 3.
Citation Information
Patent Citations
Conjugated organic microporous polymer and preparation method thereof
CN113265039A
Preparation and application of three-dimensional covalent organic polymer with electrocatalytic hydrogen peroxide production performance
CN116355212A
Lithium-sulfur battery preparation method based on hydroxyl amination covalent organic framework diaphragm
CN117673654A
Preparation method and application of covalent organic framework self-supporting diaphragm
CN117878528A
